Durvalumab and tremelimumab with or without stereotactic body radiation therapy in relapsed small cell lung cancer: a randomized phase II study. Issue 2 (21st December 2020) - Pakkala, Suchita; Higgins, Kristin; Chen, Zhengjia; Sica, Gabriel; Steuer, Conor; Zhang, Chao; Zhang, Guojing; Wang, Shuhua; Hossain, Mohammad S; Nazha, Bassel; Beardslee, Tyler; Khuri, Fadlo R; et al.
Abstract : Background: Immune checkpoint blockade (ICB) targeting programmed cell death protein 1 and cytotoxic T lymphocyte-associated protein 4 has achieved modest clinical activity as salvage therapy in relapsed small cell lung cancer (SCLC). We conducted this signal-finding study to assess the efficacy of ICB with or without radiation in relapsed SCLC. Methods: Patients with relapsed SCLC and ≤2 previous lines of therapy were randomized to (1) arm A: durvalumab (D) 1500 mg/tremelimumab (T) 75 mg (intravenously every 4 weeks without stereotactic body radiation therapy (SBRT)) or (2) arm B: immune-sensitizing SBRT to one selected tumor site (9 Gy × 3 fractions) followed by D/T. Treatment continued until progression or a maximum of 12 months. The co-primary endpoints of the study were overall response rate (ORR) and progression-free survival (PFS). We evaluated circulating lymphocyte repertoire in serial peripheral blood samples and tumor infiltrating lymphocytes (TILs) from on-treatment biopsies as pharmacodynamic markers. Results: Eighteen patients were randomized to arms A and B (n=9 each): median age 70 years; 41.2% women. The median PFS and ORR were 2.1 months and 0% in arm A and 3.3 months and 28.6% in arm B. The median overall survival (OS) was 2.8 months in arm A and 5.7 months in arm B (p=0.3772). Pooled efficacy of D/T±SBRT in 15 Response evaluation criteria in solid tumors (RECIST) evaluable patients across both arms showed the best ORR in terms of partial response in 13.3%, stable disease in 26.6% and progressive disease in 60.0%; the overall median PFS and OS were 2.76 and 3.9 months. The most common adverse events were grade 1 fatigue (66%) and grade 1 elevated amylase (56%) in arm A, and grade 1 fatigue (56%) and pain (44%) in arm B. There was a significant increase in activated CD8(+)ICOS+ T cells (p=0.048) and a reduction in naïve T cells (p=0.0454) in peripheral blood following treatment, along with a significant amount of activated CD8+ICOS+ T cells in TILs from responders. Conclusions: The D/T combination with and without SBRT was safe but did not show sufficient efficacy signal in relapsed SCLC. Changes in peripheral blood lymphocyte and TILs were consistent with an immunologic response. Trial registration number NCT02701400 .